Power relations among political actors in Relief-rehabilitation responses for Yolanda survivors in Estancia, Iloilo 2013-2015. - Deblois, Chelna Ann N.
The study analyzes the power relations among local government unit, local non-governmental organizations, and international non-governmental organizations on the relief and rehabilitation responses for Yolanda survivors. The impact of the typhoon last November 8, 2013 devastated the lives of the people in Estancia, Iloilo. This study aims to identify the issues and concerns of the survivors, the relief and rehabilitation efforts of the implementing actors and to analyze the dynamics of their power relations. We gathered data through narratives in open-ended form, documents from implementing actors, and archival research. Our findings show that the survivors are still facing the issues of displacement of houses, loss of livelihood, and drastic changes in lifestyle. The actors provided different perception on the evaluation of relief and rehabilitation. They have different views towards the current status of the survivors. Inter-organizational perceptions provided descriptions of distinct characteristics of each implementing actors. All in all, there are indeed massive responses from the implementing actors, yet the status of Yolanda survivors is questionable as they are still victims of societal issues in the system they are facing. There is a shallow coordination process between actors which leads to dissatisfaction of the survivors in terms of their present situation. The power relations should be centered to the survivors and not of the interests of the implementing actors. The survivors need to realize that they hold the greater power in the relief and rehabilitation process than the implementing actors.